2018
DOI: 10.1097/jsm.0000000000000421
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Rosenbaum Concussion Knowledge and Attitudes Survey in Collegiate Athletes

Abstract: The CKI is a valid and reliable measure in collegiate student-athletes. However, the results of the Confirmatory Factor Analysis indicated a poor model fit and improper correlations between attitude items. Therefore, the CAI may not be a sound outcome measure of collegiate student-athlete's attitudes toward concussions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 16 publications
0
41
1
Order By: Relevance
“…The authors found a mean knowledge (CKI) score of 16.4 (SD=2.9) and a mean attitude (CAI) score of 59.6 (SD=8.5), which is lower than in our sample 18. Two other studies about concussion knowledge and attitude by means of the RoCKAS were recently conducted among collegiate and kickboxing athletes (18 years of age or older) 19 20. In 430 collegiate athletes from a variety of sports, the mean knowledge (CKI) score was 19.7 (SD=2.2) and the mean attitude (CAI) score was 58.6 (SD 8.0), while those scores among 193 competitive kickboxing athletes were 19.5 (SD=2.3) and 62.7 (SD=7.4), respectively 19 20.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…The authors found a mean knowledge (CKI) score of 16.4 (SD=2.9) and a mean attitude (CAI) score of 59.6 (SD=8.5), which is lower than in our sample 18. Two other studies about concussion knowledge and attitude by means of the RoCKAS were recently conducted among collegiate and kickboxing athletes (18 years of age or older) 19 20. In 430 collegiate athletes from a variety of sports, the mean knowledge (CKI) score was 19.7 (SD=2.2) and the mean attitude (CAI) score was 58.6 (SD 8.0), while those scores among 193 competitive kickboxing athletes were 19.5 (SD=2.3) and 62.7 (SD=7.4), respectively 19 20.…”
Section: Discussioncontrasting
confidence: 67%
“…Two other studies about concussion knowledge and attitude by means of the RoCKAS were recently conducted among collegiate and kickboxing athletes (18 years of age or older) 19 20. In 430 collegiate athletes from a variety of sports, the mean knowledge (CKI) score was 19.7 (SD=2.2) and the mean attitude (CAI) score was 58.6 (SD 8.0), while those scores among 193 competitive kickboxing athletes were 19.5 (SD=2.3) and 62.7 (SD=7.4), respectively 19 20. By comparison to these two studies, it seems that the mean knowledge (CKI) and attitude (CAI) scores in the professional footballers enrolled in our study were similar, both before (pretest) and after (post-test).…”
Section: Discussionmentioning
confidence: 99%
“…Other areas of concern included difficulty in distinguishing between some of the legitimate and distractor symptoms of concussion. Recent research by Chapman et al concluded that the CAI was not a valid measure of concussion attitude in collegiate athletes [14]. The greatest limitation for the current study was having a weak correlation between these two measures and the CAI being recently found not to be a sound measure in collegiate athletes [14]; thus the results cannot be generalized.…”
Section: Resultsmentioning
confidence: 58%
“…Recent research by Chapman et al concluded that the CAI was not a valid measure of concussion attitude in collegiate athletes [14]. The greatest limitation for the current study was having a weak correlation between these two measures and the CAI being recently found not to be a sound measure in collegiate athletes [14]; thus the results cannot be generalized. Limitations of the current study was that incomplete questionnaires lead to a decrease in sample size and the questionnaire was only available in English could have influenced the responses.…”
Section: Resultsmentioning
confidence: 58%
“…Concussion knowledge and attitudes were measured using the previously validated RoCKAS-ST (Rosenbaum & Arnett, 2010 ; Chapman et al, 2018 ). The instrument comprises 55 items, from which Concussion Knowledge Index (CKI) and Concussion Attitude Index (CAI) composite scores are derived.…”
Section: Methodsmentioning
confidence: 99%